Hydrogel for hemostasis and manufacturing method thereof
Patent Information
- Application Number
- KR1020230100624
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2043-08-01
Smart Images

Figure 112023084926503-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to the development of a hemostatic patch medical device using a hydrogel material. Background Technology
[0002] Although various technologies for medical devices for hemostasis utilizing conventional hydrogels have been reported, they are not effective for long-term tissue regeneration and treatment within the body. For the clinical application of actual medical devices, there are limitations to actual commercialization because it is required that not only therapeutic effects but also the physical properties of the hydrogel be maintained for a long period in the in vivo environment.
[0003] Patent Document 1 relates to the development of a high-toughness hydrogel through heterogeneous polymer chains. In this case, the short-chain polymers break to dissipate fracture energy, thereby exhibiting high toughness of the entire hydrogel through the long-chain polymers. Graphene oxide was added to this high-toughness hydrogel and applied as a bioelectronic device.
[0004] However, the hydrogel of Patent Document 1 has the problem that it cannot recover its original function when fracture occurs. In addition, the hydrogel of Patent Document 1 is susceptible to swelling caused by water, and there is a problem that if water penetrates, the original mechanical properties and function may be deformed. Prior art literature
[0005] U.S. Patent Application Publication No. 2020-0299466 A1 (Published September 24, 2020) The problem to be solved
[0006] One objective of the present invention is to develop a hemostatic hydrogel material that can stably adhere to the human body and function for a long period of time.
[0007] Another objective of the present invention is to dramatically improve the physical properties and functions of hydrogel materials to establish a new foundation for materials for wearable bioelectronic devices. means of solving the problem
[0008] According to one aspect of the present invention, a hemostatic hydrogel comprising cross-linked poly(vinyl alcohol) (PVA); and cross-linked polyacrylic acid (Poly(acrylic acid)) (PAA) may be provided.
[0009] According to another aspect of the present invention, a method for manufacturing a hemostatic hydrogel may be provided, comprising the steps of: crosslinking polyvinyl alcohol to form a primary hydrogel; and adding polyacrylic acid to the primary hydrogel to form a secondary hydrogel. Effects of the invention
[0010] A hydrogel according to one embodiment of the present invention can recover to its original state based on self-healing power even if it suffers mechanical damage.
[0011] A hydrogel according to another embodiment of the present invention does not swell due to water, so it can maintain its original mechanical properties even in a moist tissue environment.
[0012] A hydrogel according to another embodiment of the present invention can be soft (E < ~100 kPa) and have high toughness.
[0013] A hydrogel according to another embodiment of the present invention has a Young's modulus of tens of kPa, allowing it to make conformal contact with soft biological tissues while maintaining its shape and function even in a dynamic biological environment.
[0014] A hemostatic hydrogel patch according to another embodiment of the present invention may have a relatively fast hemostatic ability (<10 sec) compared to a previously developed hemostatic hydrogel patch. Brief explanation of the drawing
[0015] FIG. 1 is a schematic diagram of a method for manufacturing a hydrogel according to one embodiment of the present invention. Figure 2 is a graph showing the results of a thermogravimetric measurement of a hydrogel according to one embodiment of the present invention. Figure 3 is a graph showing the results of measuring the gel fraction of a hydrogel according to one embodiment of the present invention. Figure 4 is a graph showing the results of a tensile test of a hydrogel according to one embodiment of the present invention. Figure 5 is a graph showing the results of measuring the Young's modulus of a hydrogel material according to one embodiment of the present invention. Figure 6 is a graph showing the results of a tensile compression test of a hydrogel according to one embodiment of the present invention. Figure 7 is a graph showing the self-healing efficiency of a hydrogel according to one embodiment of the present invention. FIG. 8 is a diagram showing the non-swelling characteristics of a hydrogel according to one embodiment of the present invention. Figure 9 is a photograph showing the tissue adhesion of a hydrogel according to one embodiment of the present invention. FIG. 10 is another photograph showing the tissue adhesion of a hydrogel according to one embodiment of the present invention. FIG. 11 is a diagram showing the results of toxicity evaluation and biocompatibility testing using fibroblasts of a hydrogel according to one embodiment of the present invention. Figure 12 is a graph showing the quantitative evaluation of cytotoxicity of a hydrogel according to one embodiment of the present invention using a CCK-8 kit. FIG. 13 is a diagram showing the results of a hemocompatibility test of a hydrogel according to one embodiment of the present invention. FIG. 14 is a diagram showing the results of an in vitro hemostasis experiment of a hydrogel according to one embodiment of the present invention. FIG. 15 is a diagram showing the performance of inhibiting an antimicrobial membrane due to bacterial attachment of a hydrogel according to one embodiment of the present invention. FIG. 16 is a diagram showing the antibacterial performance of a hydrogel according to one embodiment of the present invention. FIG. 17 is a diagram showing the antibacterial performance and biocompatibility of a hydrogel according to one embodiment of the present invention. Figure 18 is a graph showing the results of evaluating the hepatotoxicity of a hydrogel according to one embodiment of the present invention. FIGS. 19 and 20 are drawings showing the results of evaluating the hemostatic performance of a hydrogel according to one embodiment of the present invention. FIG. 21 is a diagram showing the blood coagulation ability of a hydrogel according to one embodiment of the present invention. FIG. 22 is a graph showing the degree of hemostasis of a hydrogel according to one embodiment of the present invention. Specific details for implementing the invention
[0016] The above objectives, other objectives, features, and advantages will be easily understood through the following preferred embodiments associated with the accompanying drawings. However, the embodiments described herein are not limited to those described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and that the technical concept is sufficiently conveyed to a person skilled in the art.
[0017] In describing each drawing, similar reference numerals have been used for similar components. In the attached drawings, the dimensions of the structures are depicted enlarged from their actual size for clarity of the invention. Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the invention, the first component may be named the second component, and similarly, the second component may be named the first component. A singular expression includes a plural expression unless the context clearly indicates otherwise.
[0018] In this specification, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof. Furthermore, when a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only the case where it is "immediately above" the other part, but also the case where there is another part in between. Conversely, when a part such as a layer, film, region, or plate is described as being "below" another part, this includes not only the case where it is "immediately below" the other part, but also the case where there is another part in between.
[0020] According to one embodiment of the present invention, a hemostatic hydrogel comprising cross-linked poly(vinyl alcohol) (PVA) and cross-linked polyacrylic acid (Poly(acrylic acid)) (PAA) may be provided.
[0022] According to one embodiment of the present invention, polyvinyl alcohol can be reversibly crosslinked by tannic acid (TA).
[0024] According to one embodiment of the present invention, polyacrylic acid can form a locally aggregated nanocompartment structure through hydrophobic-hydrophilic phase separation with tannic acid.
[0026] According to one embodiment of the present invention, polyacrylic acid can be crosslinked based on covalent bonds by a polymerization initiator. For example, disulfide covalent crosslinking can be formed by a polymerization initiator added to a secondary hydrogel production process.
[0028] According to another aspect of the present invention, a method for manufacturing a hemostatic hydrogel may be provided, comprising the steps of: cross-linking polyvinyl alcohol to form a primary hydrogel; and adding polyacrylic acid to the primary hydrogel to form a secondary hydrogel.
[0030] FIG. 1 is a schematic diagram of a method for manufacturing a hydrogel according to one embodiment of the present invention.
[0032] Referring to Fig. 1, polyvinyl alcohol (PVA) is crosslinked to form a primary hydrogel mixed with tannic acid (TA). Subsequently, polyacrylic acid (PAA) added to the primary hydrogel is crosslinked to form a secondary hydrogel. The primary hydrogel can form weak and reversible bonds through physical crosslinking. The secondary hydrogel can form strong and reversible bonds through chemical crosslinking.
[0034] As can be seen in Figure 1, polyvinyl alcohol (PVA) has short polymer chains and can sacrificially dissipate the force applied to the secondary hydrogel. As a result, the secondary hydrogel can have strong toughness. In addition, polyacrylic acid (PAA) has long polymer chains and can maintain the overall structure of the secondary hydrogel.
[0036] Although not illustrated in FIG. 1, tannic acid contains hydroxyl groups and hydrophobic aromatic hydrocarbons. As a result, based on its abundant hydroxyl groups, tannic acid can induce reversible crosslinking within the hydrogel, thereby enabling the hydrogel to possess toughness, elasticity, and self-healing capabilities. Additionally, through its hydrophobic aromatic hydrocarbons, tannic acid can prevent the secondary hydrogel from swelling in water. Furthermore, based on its numerous hydroxyl groups, tannic acid can interact with hemostatic factors in the body (globulin, albumin, and coagulation factors) to produce a rapid hemostatic effect.
[0038] According to one embodiment of the present invention, polyvinyl alcohol can be reversibly crosslinked by tannic acid.
[0040] According to one embodiment of the present invention, polyacrylic acid can form a locally aggregated nanocompartment structure through hydrophobic-hydrophilic phase separation with tannic acid.
[0042] According to one embodiment of the present invention, polyacrylic acid can be crosslinked based on covalent bonds by a polymerization initiator. For example, disulfide covalent crosslinking can be formed by a polymerization initiator added to a secondary hydrogel production process.
[0044] Hereinafter, the present invention will be explained in more detail through examples and experimental examples to aid in understanding the invention. However, the following examples and experimental examples are provided merely to facilitate a better understanding of the invention, and the content of the invention is not limited by the following examples and experimental examples.
[0046] [Example] Method for preparing a hydrogel
[0047] Process 1: Primary Hydrogel Preparation and Drying Process
[0048] This process refers to the process of preparing a primary hydrogel mixed with tannic acid that forms reversible cross-links with a hydrophilic polymer prior to preparing the secondary hydrogel to be described later.
[0049] Mix Component 1 with Component 2 at a ratio of 20% (w / v; weight / volume) and mix with a magnetic stirrer at 90 °C for 20 minutes. Then, add Component 3 at an additional ratio of 20% (w / v) and mix with a magnetic stirrer at 90 °C for 2 hours. Afterward, leave the mixture at -20 °C for 8 hours. Then, dry at 25 °C for 4 hours and spread thinly, followed by additional drying sequentially at 37 °C for 1 hour and 100 °C for 1 hour.
[0051] Component 1 is deionized water and is used as a solvent for a hydrogel mixed with components 2 and 3.
[0052] Component 2 is poly(vinyl alcohol) and acts as a short polymer chain of the secondary hydrogel to be described later, sacrificially dissipating the force applied to the secondary hydrogel by crosslinking with Component 3, thereby enabling the secondary hydrogel to have strong toughness.
[0053] Component 3 is tannic acid, which reversibly crosslinks within the hydrogel based on its abundant hydroxyl groups, thereby imparting toughness, elasticity, and self-healing capabilities to the secondary hydrogel. Additionally, it possesses hydrophobic aromatic hydrocarbons, which prevent the secondary hydrogel from swelling in water. Furthermore, it is known to exhibit a rapid hemostatic effect by interacting with endogenous hemostatic factors (globulin, albumin, and coagulation factors) based on its numerous hydroxyl groups.
[0055] Process 2: Secondary Hydrogel Fabrication Process
[0056] This process additionally infiltrates a hydrophilic polymer acting as a long chain into the dried primary hydrogel prepared in the first process, causing hydrophobic-hydrophilic phase separation to generate a nanocompartment structure locally aggregated with tannic acid, thereby maintaining the overall structure of the hydrogel.
[0057] In this process, the dried primary hydrogel prepared in the first process is immersed in a mixed solution of component 1, component 2, and component 3 for 2 hours. Afterward, it is heat-treated at 70 °C to induce polymerization and crosslinking. Subsequently, it is washed by immersing it in component 4.
[0058] Component 1 is poly(acrylic acid) and is used as a solvent for a hydrogel mixed with components 2, 3, and 4.
[0059] Component 2 is 2,2′-azobis(2-methylpropionamidine) dihydrochloride, and initiates the polymerization of Component 1 in a 70 °C environment.
[0060] Component 3 is N,N′-bis(acryloyl)cystamine, and it covalently crosslinks Component 1.
[0061] Component 4 is deionized water.
[0063] [Experimental Example]
[0064] Verification of Hydrogel Double Network
[0065] FIG. 2 is a graph showing the results of a thermogravimetric measurement of a hydrogel according to one embodiment of the present invention, FIG. 3 is a graph showing the results of a gel fraction measurement of a hydrogel according to one embodiment of the present invention, FIG. 4 is a graph showing the results of a tensile test of a hydrogel according to one embodiment of the present invention, FIG. 5 is a graph showing the results of a Young's modulus measurement of a hydrogel material according to one embodiment of the present invention, and FIG. 6 is a graph showing the results of a tensile compression test of a hydrogel according to one embodiment of the present invention.
[0067] As can be seen in FIGS. 2 and 3, a double network (DN) is confirmed in the material according to the present invention through thermogravimetric analysis and gel fraction. Referring to FIGS. 4 to 6, it was verified that the double network (DN) effectively dissipates fracture energy, exhibiting elasticity and high toughness while maintaining a low Young's modulus of ~100 kPa.
[0069] Confirmation of self-healing efficiency, non-swelling properties, and tissue adhesion of hydrogel
[0070] FIG. 7 is a graph showing the self-healing efficiency of a hydrogel according to one embodiment of the present invention, FIG. 8 is a diagram showing the non-swelling characteristics of a hydrogel according to one embodiment of the present invention, FIG. 9 is a photograph showing the tissue adhesion of a hydrogel according to one embodiment of the present invention, and FIG. 10 is another photograph showing the tissue adhesion of a hydrogel according to one embodiment of the present invention.
[0072] As can be seen in FIG. 7, the rapid self-healing ability (~5 minutes) of the hydrogel according to one embodiment of the present invention was verified. In addition, referring to FIG. 8, it was confirmed that the hydrogel according to one embodiment of the present invention has the characteristic of not swelling even in a moist environment.
[0074] As can be seen in FIG. 9, excellent adhesion was observed between the hydrogel according to one embodiment of the present invention and commercially available pig skin. Furthermore, referring to FIG. 10, it was confirmed that the hydrogel according to one embodiment of the present invention was perfectly attached to the pig skin without any areas where it partially detached, not by simply photographing the adhesion, but by using a scanning electron microscope (SEM).
[0076] Toxicity assessment and biocompatibility verification of hydrogels
[0077] FIG. 11 is a diagram showing the results of toxicity evaluation and biocompatibility experiments using fibroblasts of a hydrogel according to one embodiment of the present invention, and FIG. 12 is a graph showing the cytotoxicity evaluation of a hydrogel according to one embodiment of the present invention quantitatively using a CCK-8 kit.
[0079] Referring to Fig. 11, as a toxicity evaluation and biocompatibility test using fibroblasts, live and dead kit assays and Phalloidin were used as biomarkers. It was confirmed that the hydrogel according to one embodiment of the present invention, despite having a lubricant applied to its coating, was non-toxic and did not affect cell differentiation through fibroblasts. Additionally, referring to Fig. 11, the cytotoxicity evaluation was quantitatively shown using the CCK-8 kit.
[0081] Confirmation of hydrogel's blood compatibility and blood coagulation ability
[0082] FIG. 13 is a diagram showing the results of a hemocompatibility test of a hydrogel according to one embodiment of the present invention, and FIG. 14 is a diagram showing the results of an in vitro hemostasis test of a hydrogel according to one embodiment of the present invention.
[0084] Referring to FIG. 13, the extent to which red blood cells are destroyed by low osmotic pressure in order for the hydrogel according to one embodiment of the present invention to be used as a hemostatic material was proven through a hemocompatibility test. As can be seen from the experimental results, it was confirmed that no hemolysis occurred in the final composition of the hydrogel according to one embodiment of the present invention, TA / PAA / PVA.
[0086] Referring to FIG. 14, it can be seen that the hydrogel according to one embodiment of the present invention showed excellent blood coagulation ability only in the TA / PVA / PAA group containing tannic acid in an in vitro hemostasis experiment.
[0088] Confirmation of the antimicrobial membrane inhibitory and antibacterial performance of the hydrogel
[0089] FIG. 15 is a diagram showing the performance of inhibiting an antimicrobial membrane due to bacterial attachment of a hydrogel according to one embodiment of the present invention, and FIG. 16 is a diagram showing the antibacterial performance of a hydrogel according to one embodiment of the present invention.
[0091] As shown in Fig. 15, the results of evaluating the antimicrobial membrane inhibition performance based on bacterial adhesion show that the hydrogel according to one embodiment of the present invention exhibits excellent antimicrobial performance against both Gram-positive and Gram-negative bacteria. In Fig. 16, alkaline phosphatase was tested using a test kit, and calcium was tested by staining with Alizarin red S. It can be seen that antimicrobial performance was observed only in the groups containing tannic acid (TA / PVA, TA / PVA / PAA).
[0093] Confirmation of antimicrobial performance and biocompatibility of hydrogel
[0094] FIG. 17 is a diagram showing the antibacterial performance and biocompatibility of a hydrogel according to one embodiment of the present invention, and FIG. 18 is a graph showing the results of evaluating the hepatotoxicity of a hydrogel according to one embodiment of the present invention.
[0096] Referring to FIG. 17, the biocompatibility and antimicrobial membrane inhibition performance of a hydrogel according to one embodiment of the present invention were evaluated through insertion into mouse subcutaneous skin tissue. While a general substrate is susceptible to bacterial adhesion and easily forms a biofilm, it can be seen that the hydrogel according to one embodiment of the present invention exhibits excellent antimicrobial performance and biocompatibility.
[0098] Figure 18 shows the evaluation of hepatotoxicity through subcutaneous skin tissue insertion. It was confirmed that there was no hepatotoxicity in the evaluation of Alanine aminotransferase (ALT) and Aspartate aminotransferase (AST).
[0100] Confirmation of hemostatic performance of hydrogel
[0101] FIGS. 19 and 20 are drawings showing the results of evaluating the hemostatic performance of a hydrogel according to one embodiment of the present invention, FIG. 21 is a drawing showing the blood coagulation ability of a hydrogel according to one embodiment of the present invention, and FIG. 22 is a graph showing the degree of hemostasis of a hydrogel according to one embodiment of the present invention.
[0103] Referring to FIGS. 19 and 20, holes were made in the livers of mice, and a hydrogel according to one embodiment of the present invention (TA / PVA / PAA) and a highly biocompatible general hydrogel (PVA) were attached to the perforated liver tissue to evaluate hemostatic performance. In the case of the general hydrogel, no hemostatic effect was observed, with no difference from the untreated (NT) group. On the other hand, the hydrogel according to one embodiment of the present invention demonstrated excellent hemostatic performance.
[0105] Referring to FIG. 21, the degree of blood coagulation was compared by photographing the surfaces of a general hydrogel (PVA) and a hydrogel (TA / PVA / PAA) according to one embodiment of the present invention using SEM images. It can be seen that only the surface of the hydrogel according to one embodiment of the present invention exhibited superior blood coagulation ability. FIG. 22 quantitatively shows the degree of hemostasis.
Claims
Claim 1 A hemostatic hydrogel comprising crosslinked poly(vinyl alcohol) (PVA); and crosslinked polyacrylic acid (PAA), wherein the poly(vinyl alcohol) is reversibly crosslinked by tannic acid (TA), the hydrophobic aromatic hydrocarbons of tannic acid prevent the hemostatic hydrogel from swelling by water, the numerous hydroxyl groups of tannic acid interact with hemostatic factors in the body to exhibit a hemostatic effect, and the polyacrylic acid forms a locally aggregated nanocompartment structure through hydrophobic-hydrophilic phase separation with tannic acid. Claim 2 delete Claim 3 delete Claim 4 A hemostatic hydrogel according to claim 1, wherein the polyacrylic acid is cross-linked based on covalent bonding by a polymerization initiator. Claim 5 A method for manufacturing a hemostatic hydrogel according to claim 1, comprising: a step of forming a primary hydrogel by crosslinking polyvinyl alcohol; and a step of forming a secondary hydrogel by adding polyacrylic acid to the primary hydrogel, wherein the polyacrylic acid forms a locally aggregated nanocompartment structure through hydrophobic-hydrophilic phase separation with tannic acid. Claim 6 delete Claim 7 delete Claim 8 A method for manufacturing a hemostatic hydrogel according to claim 5, wherein the polyacrylic acid is cross-linked based on covalent bonding by a polymerization initiator.
Citation Information
Patent Citations
Composition for polymer gel, gel prepared from composition and application of gel
CN112341637A
Biocompatible adhesives and methods of use thereof
EP3432933B1
Biomedical tissue adhesive and preparation method thereof
CN116059434A
Adhesive material with triggerable on-demand separation
KR1020230071113A
